Failure Analysis - Huang, Zheng-Ming; Hemeda, Sayed (IntechOpen, 2019)
This book, Failure Analysis, covers a broadest sense failure to a narrowest sense one. One purpose of this book is to provide the reader with an overall picture of various failures and how to deal with them. Another purpose is to present the latest scientific advancements in this field. For instance, an innovative concept of true stresses is introduced and is shown to be necessary in dealing with a composite failure micromechanically.